Peningkatan Minat Literasi Siswa/i Desa Limbungan dalam Menciptakan Keamanan Pendidikan - Muh. Ade Safri Salampessy; Hidayat Chusnul Chotimah (Jurnal ABDI RAKYAT, 2024)
One of the regions of Indonesia that has issues with educational fairness is the eastern region, particularly with the distribution of educators like teachers or tutors. The East Lombok Region's Limbungan Village is one of the places where this issue is present. So, Universitas Teknologi Yogyakarta’s Community Service Team chose it’s location as the focus of community service efforts to combat that problems. In this instance, the Community Service Team and Indonesia in Village worked together to carry out community service by focusing on educational issues through the "Suar Desa Adat Limbungan" program with the theme "Increasing Literacy Interest in Students of Limbungan Village in Creating Educational Security through the Concept of Human Security." This service activity comprises of five basic activities: Atraksi, Atraktif, Aksi, Selam, and Book Donation. It is believed that Limbungan Village would be able to address structural issues and other issues faced by local inhabitants as a consequence of community service activities.